Construction of nested real ideal lattices for interference channel coding - Trinca Watanabe, C. C.; Belfiore, J. C.; De Carvalho, E. D. [UNESP]; Vieira Filho, J. [UNESP]; Watanabe, R. A. (Academic Publications, 2019)
In this work we develop a new algebraic methodology which quantizes real-valued channels in order to realize interference alignment (IA) onto a real ideal lattice. Also we make use of the minimum mean square error (MMSE) criterion to estimate real-valued channels contaminated by additive Gaussian noise.
Keywords: Channel quantization; Interference alignment; Maximal real subfield; Real nested ideal lattices